ANALISIS KINERJA KOPERASI BERDASARKAN PERATURAN MENTERI NEGARA KOPERASI DAN USAHA KECIL DAN MENENGAH REPUBLIK INDONESIA NOMOR : 06/PER/M.KUKM/V/2006 (Studi Kasus Pada Koperasi Karyawan PT Gudang Garam, Tbk “MEKAR” Kediri Periode 2011-2013) - Dimas Kurniawan (Fakultas Ilmu Administrasi Universitas Brawijaya, 2015)
Cooperative performance is one factor that must be taken to ensure that the purpose of the cooperative to run well. Cooperative aims to improve the welfare of members in particular and society in general. The study was conducted to assess the performance of the cooperative based on the Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number: 06 / Reg/ M.CSME / V / 2006. Location study on Cooperative Employees (Kopkar) PT Gudang Garam, Tbk